DZIELIMY SIĘ DOŚWIADCZENIEMMitral insufficiency and aortic arch aneurysm in a woman with Marfan syndrome treated twice in the cardiac surgery unit - Bilewska, Agata; Kuśmierczyk, Mariusz; Michałowska, Ilona; Hoffman, Piotr; Różański, Jacek M. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Marfan syndrome is an autosomal dominant disorder of the connective tissue. Mutation in the fibrillin gene locus is believed to be responsible for impaired structural integrity of the elastin network. Symptoms of Marfan syndrome involve the skeletal, ocular and cardiovascular systems. We report a case of a 26-year-old woman with Marfan syndrome referred for surgical treatment because of mitral insufficiency and aortic aneurysm. The patient was operated on twice. As a 12-year-old girl she underwent aortic root replacement with composite graft (Bentall-de Bono procedure). After 7 years she was reoperated on. The third operation involved mitral valve replacement and resection of the ascending aorta and the arch due to a large aneurysm located distally to the previous anastomosis. The cardiopulmonary bypass was initiated through the innominate artery. A few weeks after the operation the patient required vacuum-assisted therapy due to sternal wound infection.